Duane syndrome: An overview on the current management - Priyanka Prasad; Abhyuday Saxena; Rohit Saxena (Taiwan Journal of Ophthalmology, 2023)
Duane syndrome is one of the most common restrictive congenital strabismus characterized by variable horizontal duction deficits with globe retraction and shoots on attempted adduction and narrowing of the palpebral aperture. It is now listed as a congenital cranial dysinnervation disorder. The disease is usually unilateral with female preponderance. Basic etiopathogenesis involves dysinnervation of the lateral rectus (LR) due to aplastic/hypoplastic abducens nucleus with a secondary aberrant supply to the LR by the medial rectus (MR) subnucleus of the oculomotor nerve. Diagnosis of the disease is usually clinical. Due to the variable presentation of the disease, surgical management is a challenge and has to be individualized to achieve alignment in the primary gaze, reduction in globe retraction, upshoots and downshoots, and correction of any abnormal head posture. Differential recessions of the lateral and MR muscles are done to correct esotropia or exotropia in the primary gaze. For globe retraction and shoots, Y-split or periosteal fixation of the LR muscles is done depending on the severity.